2021
DOI: 10.25165/j.ijabe.20211404.6281
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of salmon (Salmo salar) quality during refrigeration storage based on dielectric properties

Abstract: Dielectric properties are validated to be correlated with the changes of food quality during 4°C storage, thus it could be used as predictive indicators for the quality parameters of salmon (Salmo salar) during cold storage. An open-ended coaxial detection method was used to determine the dielectric properties (dielectric constant ε' and dielectric loss ε") of salmon at the frequency range of 20-2500 MHz, and to explore the relationship between dielectric properties and volatile base nitrogen (TVB-N), thiobarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…On the other hand, a study with salmon stored in refrigeration conditions showed that both the dielectric constant and loss factor increased along with storage time [ 54 ]. The dielectric loss showed a significant correlation with quality indexes including total volatile basic nitrogen (TVB-N), which is an indicator of the degree of protein degradation, at five selected frequencies (27.12, 40.68, 100, 300, and 915 MHz) [ 54 ]. Dielectric properties might be affected by an increase in metabolites and free ions, but also by the loss of free water [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a study with salmon stored in refrigeration conditions showed that both the dielectric constant and loss factor increased along with storage time [ 54 ]. The dielectric loss showed a significant correlation with quality indexes including total volatile basic nitrogen (TVB-N), which is an indicator of the degree of protein degradation, at five selected frequencies (27.12, 40.68, 100, 300, and 915 MHz) [ 54 ]. Dielectric properties might be affected by an increase in metabolites and free ions, but also by the loss of free water [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric loss showed a significant correlation with quality indexes including total volatile basic nitrogen (TVB-N), which is an indicator of the degree of protein degradation, at five selected frequencies (27.12, 40.68, 100, 300, and 915 MHz) [ 54 ]. Dielectric properties might be affected by an increase in metabolites and free ions, but also by the loss of free water [ 54 ]. A similar effect might have occurred with octopus with the increase in immersion time.…”
Section: Resultsmentioning
confidence: 99%